Native Americans and Palestinians Occupation, Exile, and Resistant Poetry - Muyassr Qasim Al-khashab (PROSPECTIVE RESEARCHES, 2023)
This study analytically presents a clear description of similar experience and responses of dispossession of people in North America and Palestine. Native Americans (the Red Indians) and Palestinians have both faced the same situation of colonization; the first one by the Europeans (the white), and the second one by the Zionists. The conditions of Native Americans, isolated in reservations within the boundaries of their native land, are extensively similar to the current situation of Palestinians, who are compelled to stay in refugee camps, and Arab ghettoes inside the borders of Palestine. One can easily observe other points of convergence and divergence between them, not only in the processes of events, but also in the subject of writing poetry; the feeling of nostalgia, and the idea of resistance. The objective is to show both the victims of those two unfairly ruled and oppressed nations by the occupants.